Evaluation of definitions for oral anticoagulant-associated major bleeding: A population-based cohort study. Issue 213 (May 2022) - Xu, Yan; Gomes, Tara; Wells, Philip S.; Pequeno, Priscila; Johnson, Ana; Sholzberg, Michelle
Abstract: Introduction: Major bleeding is the most serious complication of oral anticoagulants (OACs). While consensus criteria to define major bleeding have been established by the International Society for Thrombosis and Haemostasis (ISTH), Bleeding Academic Research Consortium (BARC) and Thrombolysis in Myocardial Infarction (TIMI), significant variability exists across these definitions. We sought to evaluate the agreement of cases identified by the three definitions and to assess their effect on mortality and OAC resumption. Methods: We used a dataset of individuals ≥66 years in Ontario, Canada presenting with OAC-related bleeding from 2010 to 2015. For case agreement, we calculated Cohen's κ between the three major bleeding definitions. We used multivariate regression to determine differences in mortality and OAC resumption among ISTH, BARC and TIMI-defined major bleeds. Results: Among 2002 cases of OAC-related bleeding, agreement in case identification between ISTH and BARC was substantial (Cohen's κ = 0.69); however, agreement between TIMI and other definitions were poor. Using 30-day mortality of clinically relevant non-major bleeds as comparator, ISTH-, BARC- and TIMI-defined major bleeds conferred 3.3-, 3.2- and 5.9-fold increased risk. Among survivors, 50% with ISTH- and BARC-defined major bleeds resumed OACs at 180 days, compared to 31% of TIMI-associated cases. Conclusion: Major bleeds identified by ISTH and BARC criteria showed good agreement and similar prognostic utility, whereas TIMI criteria identified patients at greater clinical risk. Our results highlight the need to revise major bleeding definitions based on criteria that are independently predictive of clinically relevant morbidity and mortality to more effectively reflect the risk associated with major bleeding and appropriately influence anticoagulant therapy decisions.